127k views
0 votes
2x-(x-(2x+3)-3x-11 help plssss​

2 Answers

5 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{ - 4x - 14}}}}}

Explanation:


\sf{2x - x - (2x + 3) - 3x - 11}

When there is a ( - ) in front of parentheses in an expression, change the sign of each term


\sf{2x - x - 2x - 3 - 3x - 11}

Collect like terms


\sf{2x - x - 2x - 3x - 3 - 11}

Since the terms having opposite signs adds up to zero, remove them from the expression


\sf{ - x - 3x - 3 - 11}


\sf {- 4x - 14}

Hope I helped!

Best regards!!

User Posdef
by
5.2k points
1 vote

Answer:

I'll say x = 8

Explanation:

because Simplifying

2x + -3 = 3x + -11

Reorder the terms:

-3 + 2x = 3x + -11

Reorder the terms:

-3 + 2x = -11 + 3x

Solving

-3 + 2x = -11 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-3 + 2x + -3x = -11 + 3x + -3x

Combine like terms: 2x + -3x = -1x

-3 + -1x = -11 + 3x + -3x

Combine like terms: 3x + -3x = 0

-3 + -1x = -11 + 0

-3 + -1x = -11

Add '3' to each side of the equation.

-3 + 3 + -1x = -11 + 3

Combine like terms: -3 + 3 = 0

0 + -1x = -11 + 3

-1x = -11 + 3

Combine like terms: -11 + 3 = -8

-1x = -8

Divide each side by '-1'.

x = 8

User Scarass
by
4.7k points